Effects of injured and dead cells of Escherichia coli on the colony‐forming rate of live cells. Issue 2 (30th December 2020) - Saito, Mikako; Takatani, Norimasa; Yoshida, Tomonori; Mariogani, Alvin; Cho, Eol; Matsuoka, Hideaki
Abstract : Osmotic stress‐induced injured cells of Escherichia coli were prepared by sorting live cells onto tryptic soy agar (TSA) containing 10–50% sucrose. The time course of colony‐forming rate (CFR%) was analyzed. A time delay in colony formation indicated a sublethal effect. The final CFR level at 24 h indicated the relative number of culturable cells irrespective of injury. A value of (100‐CFR)% at 24 h indicated a lethal effect. When cells were grown on TSA containing 10% sucrose, the time delay was 4 h and the lethal effect was 4%. However, dead cells inhibited the growth of live cells. Physical contact with insoluble matter derived from dead cells or dead cells themselves might have caused growth inhibition. These findings highlight a novel perspective on colony count methods in practical situations, such as when sampling foods containing a high concentration of sucrose. Abstract : Single‐cell sorting of Escherichia coli was conducted to analyze the effect of osmotic stress–induced injury on the colony‐forming rate (CFR). Injury caused a time delay in the start of colony formation and a decrease in the final level of CFR. Surprisingly, dead cells also inhibited cell growth possibly due to the release of insoluble factors.